Efficiency Analysis using Economizer Alternative Energy in Boilers - Moh Muchlishiin; Dino Erivianto (Formosa Journal of Science and Technology, 2023)
Efficiency is one of the efforts in implementing energy conservation. Economizers are an alternative source of energy that can survive because of the potential for energy efficiency. Economizer equipment in producing electrical energy and steam produces less than 10-30% fuel needed for a conventional energy plant. The Economizer system that was assumed in this study, there was an increase in boiler efficiency with an Economizer system of 19%. As for the need for burning calories in the combustion chamber with an Economizer system of 46,868,200,68 kcal/hour compared to a system without an Economizer of 61.003.054,86 kcal/hour. Thus the fuel requirement will be less with an Economizer system of 7,735 kg/hour compared to a system without an Economizer of 10.069 kg/hour. So that the results obtained with the same ratio and type of fuel, there is a fuel efficiency of 2.334 kg/hour.